EVALUASI TINGKAT PENGETAHUAN CARDIAC ARREST BERDASARKAN KARAKTERISTIK PERAWAT DI RUMAH SAKIT “X” INDRAMAYU - Tri Elina Sari,; Rian Andriani,; Kahar Mulyani, (Journal of Innovation Research and Knowledge, 2025)
Background : Nursing knowledge is crucial in a hospital environment since nurses act as first responders in the event of cardiac arrest, hence the importance of a nurse's knowledge in providing care during an emergency. Objective: to evaluate the nurses' characteristics in improving knowledge on cardiac arrest at “X” Hospital, Indramayu. Method: using qualitative research by interviewing and observing nursing management at “X” Hospital, Indramayu. Result: similar levels of knowledge between age and gender groups. Nurses with more experience, training and higher education have better knowledge on the treatment algorithm of cardiac arrest. The ideal strategy includes training, seminars, group discussions within nursing staff and department heads, evaluation of nursing work in the hospital. Conclusion: knowledge of cardiac arrest varies among nurses, hence a strategy is needed to improve knowledge amongst nurses